Threshold manipulation in parity-time symmetric microresonator chain - Phang, Sendy; Vukovic, Ana; Creagh, Stephen; Benson, Trevor M.; Gradoni, Gabriele; Sewell, Phillip D. (2015)
This paper analyses the eigenfrequencies of an infinitely long chain of microresonators with PT symmetry. The results show that the depth of modulation of the real part of the refractive index can be used to control the threshold point of the PT structure.